Switching to Integrase Inhibitors Unlinked to Weight Increase in Perinatally HIV-Infected Young Adults and Adolescents: A 10-Year Observational Study - Taramasso, Lucia; Di Biagio, Antonio; Bovis, Francesca; Forlanini, Federica; Albani, Elena; Papaioannu, Rebecka; Giacomet, Vania (Microorganisms (Basel), 2020)
An unexpected increase in weight gain has recently been reported in the course of integrase strand transfer inhibitors (INSTI) treatment. The possibility of this effect in people who are perinatally infected with HIV (PHIV) and thus exposed to lifelong therapy needs to be explored. This is a retrospective multicenter case-control study. Adults with PHIV followed between 2010 and 2019 in two outpatient services in Northern Italy were included if they had at least two weight measures in two successive years of observation. Patients were considered as cases if they were switched to INSTI (INSTI group), or controls if they were never exposed to INSTI (non-INSTI group). The date of the switch in cases was considered to be the baseline (T0), while it was randomly selected in controls. Mixed effect models were used to assess the weight changes in INSTI and non-INSTI groups. A total of 66 participants, 50.0% women, 92.4% Caucasian, were included. Median follow-up was 9 years (range 2–10): 4 years (range 1–8) before and 3 (range 1–9) after-T0. Mean age at the last study visit was 27.3 (±4.8) years, and mean CD4+ T-cells were 820.8 (±323.6) cells/mm3. Forty-five patients were switched to INSTI during the study, while 21 remained in the non-INSTI group. The INSTI group experienced a mean increase (pre-post T0) in bodyweight of 0.28 kg/year (95% CI − 0.29; 0.85, p = 0.338), while in the non-INSTI group, the mean increase was 0.36 kg/year (95% CI − 0.47; 1.20, p = 0.391), without a significant difference between groups (p for interaction between time and treatment regimen = 0.868). Among patients on INSTI, the weight gain after T0 was higher than pre-T0, amounting to +0.28 kg/year (95% CI − 0.29; 0.85), although this difference did not reach significance (p = 0.337). PHIV switched to an INSTI-based regimen did not experience an excessive weight gain compared to those who were treated with a non-INSTI based regimen in our cohort.